EFL STUDENTS’ VIEWS AND EXPERIENCES OF CULTURE LEARNING: ARE THEY WORTHY TO FOSTER INTERCULTURAL COMPETENCE? - Marwa Marwa (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2018)
Abstract: In the light of globalization, intercultural competence is crucially demanded by the language learners to be successful speakers and mediators in international interaction and communication. This study aims at investigating how the Indonesian EFL students view and undertake the culture learning in their classrooms. This study was a survey research carried out in October and December 2016 in two state universities: 1) University of Riau (UR) located in Riau Province and 2) Brawijaya University (UB) in Malang-East Java. There were a total of 80 participants involved by using random sampling. The student questionnaire (adopted and adapted from HST. Kiet, 2011) consisting of six statements was used. To answer the research question, descriptive statistics analysis (Sum of score, Mean and Standard Deviation) was used to analyse the completed student questionnaire. The findings reveal that the students showed positive attitudes in culture learning purposes; they mainly learned cultural facts oriented to target culture exploration as the dominant cultural learning in the classroom; they used media such as internet, TV and literature as the most dominant cultural learning sources outside the classroom; they found that culture learning benefited them to their EFL learning; and finally they agreed that the target culture should be taught together with the target language in EFL classes. Therefore, it is suggested that future researchers do such an in-depth study pertaining to students’ ICC learning and development in the environment of classroom interactions.